2002
DOI: 10.1038/nn854
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive induction of caudal neural character by graded Wnt signaling

Abstract: Early in differentiation, all neural cells have a rostral character. Only later do posteriorly positioned neural cells acquire characteristics of caudal forebrain, midbrain and hindbrain cells. Caudalization of neural tissue in the chick embryo apparently involves the convergent actions of (i) fibroblast growth factor (FGF) signaling and (ii) signaling from the caudal paraxial mesoderm, or 'PMC activity', which has not yet been defined molecularly. Here we report evidence that Wnt signaling underlies PMC activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 0 publications
6
100
1
Order By: Relevance
“…strated. The requirement of an anteroposterior gradient of Wnt/␤-catenin signaling for the formation of the embryonic axis and neural plate, however, is well documented (Kiecker and Niehrs, 2001;Nordstrom et al, 2002;Lagutin et al, 2003).…”
Section: Ap Progression Of Lithium Repression Of Cardiomyogenesismentioning
confidence: 99%
“…strated. The requirement of an anteroposterior gradient of Wnt/␤-catenin signaling for the formation of the embryonic axis and neural plate, however, is well documented (Kiecker and Niehrs, 2001;Nordstrom et al, 2002;Lagutin et al, 2003).…”
Section: Ap Progression Of Lithium Repression Of Cardiomyogenesismentioning
confidence: 99%
“…Recent studies in zebrafish showed that a gradient of Wnt signaling regulates the anteroposterior partitioning of the brain with high Wnt tone inducing diencephalic fate at the expense of more anterior structures, whereas inhibition of high Wnt tone is required to induce the formation of the telencephalon and eyes (Masai et al, 1997;Heisenberg et al, 2001;Houart et al, 2002). Other studies showed regulation of anteroposterior neural fate in the neural tube as a whole in chick by Wnts (Nordstrom et al, 2002;Gunhaga et al, 2003). Taken with this earlier work, the recent study showing that Wnts are also required to properly induce posterior patterning of the diencephalon in chick supports a repeated role for Wnt signaling in regulating A-P development of several forebrain compartments during development.…”
Section: Defects In Zli Signaling Molecule Expression In Lrp6 Mutantsmentioning
confidence: 99%
“…The folding of the neural tube during gestation as the brain expands leads to the transition of these initial anteroposterior divisions into a dorsoventral orientation. Previous studies have shown that during submammalian vertebrate development, Wnt signaling is involved in the initial anteroposterior patterning of the neural tube and later in subdividing the brain into telencephalon, eye fields, and diencephalon (Heisenberg et al, 2001;Houart et al, 2002;Nordstrom et al, 2002). Also, an important functional role for Wnt signaling specifically in thalamic development has recently been suggested in chick, where Wnt signals were shown to be required at early stages to induce a posterior forebrain marker in the diencephalon and then again at later stages to induce dorsal thalamic markers within this posterior forebrain domain (Braun et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A gradient of Wnt/beta-catenin signaling is required for anterior-posterior (AP) patterning of the embryo during gastrulation and neurulation (Kiecker and Niehrs, 2001;Davidson et al, 2002;Houart et al, 2002;Nordstrom et al, 2002;Lagutin et al, 2003). A posterior to anterior gradient of Wnt signaling, with Wnts being more highly expressed posteriorly and Wnt inhibitors being more highly expressed anteriorly, results in posterior to anterior allocation of cell fate in the neural plate.…”
Section: Introductionmentioning
confidence: 99%